2011
DOI: 10.1124/dmd.110.037341
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of [14C]Brivanib Alaninate after Oral Administration to Rats, Monkeys, and Humans

Abstract: ]brivanib alaninate to intact rats, bile duct-cannulated (BDC) rats, intact monkeys, BDC monkeys, and humans. Fecal excretion was the primary route of elimination of drug-derived radioactivity in animals and humans. In BDC rats and monkeys, the majority of radioactivity was excreted in bile. Brivanib alaninate was rapidly and completely converted via hydrolysis to brivanib in vivo. The area under the curve from zero to infinity of brivanib accounted for 14.2 to 54.3% of circulating radioactivity in plasma in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…LC/MS analysis indicated that brivanib was metabolized primarily to a hydroxy metabolite with a protonated molecular ion at m/z 387. This metabolite had the same HPLC retention time, as well as MS and MS/MS fragmentation patterns, as M7 that was characterized in a previous study (Gong et al, 2011). In addition, a carboxylic acid derivative (M26) and a ketone metabolite (M31), formed at much lower levels than M7, were also observed in the incubation mixture.…”
Section: Downloaded Frommentioning
confidence: 73%
See 4 more Smart Citations
“…LC/MS analysis indicated that brivanib was metabolized primarily to a hydroxy metabolite with a protonated molecular ion at m/z 387. This metabolite had the same HPLC retention time, as well as MS and MS/MS fragmentation patterns, as M7 that was characterized in a previous study (Gong et al, 2011). In addition, a carboxylic acid derivative (M26) and a ketone metabolite (M31), formed at much lower levels than M7, were also observed in the incubation mixture.…”
Section: Downloaded Frommentioning
confidence: 73%
“…Similar to HLM-mediated metabolism, the prodrug was not observed after incubation due to rapid hydrolysis. Metabolism of brivanib in cytosol in the presence of PAPS yielded a sulfate conjugate with HPLC retention time, as well as MS and MS/MS fragmentation patterns identical to M25, a direct sulfate conjugate of brivanib characterized previously (Gong et al, 2011).…”
Section: Downloaded Frommentioning
confidence: 99%
See 3 more Smart Citations